Dinamika Psikologis Perempuan Dewasa Awal Pasca Abortus Provocatus - Bella Oktavia; Zakwan Adri (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to investigate the psychological dynamics of early adult women after a induced abortion. Using a qualitative methodology with a phenomenological approach, this study involved female participants aged 18-40 years, who were students or workers, had undergone an induced abortion, and were willing to participate. A purposive sampling technique was used to identify eligible participants. Data were collected through in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results revealed three main themes: first, psychological dynamics including feelings of guilt, depression, and anxiety after the procedure; second, factors influencing psychological dynamics, such as social support, environmental factors, and previous personal experiences; and third, self-meaning and future expectations, where most participants attempted to forgive themselves and build positive expectations for their future. This study provides in-depth insight into the psychological experiences of early adult women after a induced abortion and the importance of emotional and psychological support in the recovery process.